﻿A new occurrence species Boea clarkeana Hemsl. (Gesneriaceae Dumort) of the flora of Vietnam - Xuyen, Do Thi; Phuong, Vu Xuan (Academia Journal of Biology, 2012)
﻿According to W. T. Wang et al., 1998 [10], the genus Boea Comm. ex Lamk had about 20 species mainly distributed Asia and Australia. There were 1 Boea species in Vietnam as Boea philippensis C. B. Clarke. During the study of specimen and documents of Gesneriaceae of Vietnam, we have found one new occurrence species of Boea: Boea clarkeana Hemsl. for the flora of Vietnam, before is recorded endemic to China. B. clarkeana is herbs, near stemless. Leaves basal, leaf blade ovate to broadly ovate, elliptic or obovate, ca. 2-10 · 1.4-7 cm, with white to gray or greenish apprised pubescent, lateral veins 5-7 pairs; petiole 3-10 cm long. Inflorescences cymes; peduncle 3-18 cm long, with gray puberulent; bracts broad ovate to narrowly ovate, ca. 4-9 mm long. Calyx 6-9 mm long, 5 lobed from middle; lobes ca 3-4 · 2- 2.5 mm. Corolla white to blue or blue - purple, ca. 14-22 mm long, tube ca. 1-1.5 · 0.7-1 cm; adaxial lip 2 lobes, ca. 3 -5 mm long; abaxial lip 3 lobes, ca. 4-5 cm long. Filament 2, ca. 7 mm long, staminodes 2 or 3. Pistil 0.9-1.9 cm long; ovary 5-8 mm long, short brownish puberulent or glandular puberulent. Capsule ca. 1.8-4.5 cm long, 2 valves, spirally twisted. Seeds unappendaged. It closes with Boea philippensis but differ as petiole ca. 3-10 cm long, calyx 5 lobed from middle, corolla ca. 14-22 mm long. Voucher specimens were collected in Moc Chau district, Son La province and Mai Chau (Hoa Binh), deposited in the Herbarium of the Institute of Ecology and biological Resources, Hanoi, Vietnam (HN).